Methods of modern genetics - Tkachuk, Elena Anatolyevna; Seminsky, Igor Zhanovich (Bajkalʹskij medicinskij žurnal, 2023)
Modern genetics uses a number of methods that are its tools in understanding the essence of human hereditary pathology. Genetic methods are usually used together. Understanding the possibilities of methods for studying human genetics is the key to successful diagnosis of hereditary diseases. The lecture presents methods for studying modern genetics. It is shown that clinical genetics operates with a number of methods that allow successfully solving the tasks assigned to it. The methods of modern genetics include: genealogical, clinical, cytogenetic, molecular cytogenetic, molecular genetic, population, twin, dermatoglyphic, bioinformatic, biochemical, paraclinical, bioengineering methods and modeling method. All methods are of practical importance and help to make a diagnosis and predict the development of the disease. Methods in genetics are used in diagnostic schemes when making a diagnosis of a hereditary disease. In clinical practice, as a rule, methods with the lowest cost are used first, and then more accurate, modern, but also expensive methods are resorted to. This allows you to establish the diagnosis of even the rarest hereditary disease.